Supply Chain Redesign: Transforming Supply Chains into Integrated Value Systems - Handfield, Robert; Nichols, Ernest (Financial Times Prentice Hall books., 2002)
Supply Chain Redesign delivers practical guidance for every aspect of supply chain redesign: mapping existing supply chains; identifying changes that promise the best ROI; intelligently leveraging new technologies; strengthening relationships with key partners; designing products that support lean supply chains; implementing new approaches to strategic cost management; and much more. Coverage includes key success factors, emerging trends, and detailed case studies from Nortel and GM.